How to Measure Segregation Conditional on the Distribution of Covariates - Olof Åslund; Oskar Nordström Skans (Uppsala University, Department of Economics, 2007)
This short paper proposes a non-parametric method of accounting for the distribution of background characteristics when testing for segregation in empirical studies. It is shown and exemplifiedusing data on workplace segregation between immigrants and natives in Swedenhow the method can be applied to correct any measure of segregation for differences between groups in the distribution of covariates by means of simulation, and how analytical results can be used when studying segregation by means of peer group exposure.
urn:nbn:se:uu:diva-12431
Keywords: C10; J10; J20; 330; Segregation; Covariates; Workplaces; Immigrants; Segregation; Arbeitsplatz; Migranten; Theorie; Schweden